A novel compact dual band RFID handheld reader antenna for microwave ISM band application - Wahiba Belgacem; Miloud Bousahla; Sidi Mohammed Meriah (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This paper presents a new design of dual band RFID reader antenna for ISM-band industrial science and medical applications at 2.4 GHz and 5.8 GHz. Theantenna is designed and physically built using FR4 substrate and taking a 1.5 thickness, 4.3 relative permittivity and 0.025 loss tangents. Different slots havebeen introduced to reduce the antenna dimensions and to achieve the dual bandfor microwave ISM band application. The dimension of the proposed antenna is 34 × 34 × 1.5 mm3, which it could be easily integrated into RFID readers.Numerical simulations have been performed usingcomputer simulationtechnology (CST) Microwave Studio software. A parametric study wasinvestigated in order to show the effect of slots variation and to obtain the desiredfunctional characteristics. Experimental results show a good agreement withresults obtained by simulations. A satisfactorily omnidirectional for the radiationpatterns across the antenna operation bands was obtained.